Cardiac Imaging Using Clinical 1.5 T MRI Scanners in a Murine Ischemia/Reperfusion Model. (5th December 2010) - Voelkl, Jakob G. J.; Haubner, Bernhard J.; Kremser, Christian; Mayr, Agnes; Klug, Gert; Loizides, Alexander; Müller, Silvana; Pachinger, Otmar; Schocke, Michael; Metzler, Bernhard
Abstract : To perform cardiac imaging in mice without having to invest in expensive dedicated equipment, we adapted a clinical 1.5 Tesla (T) magnetic resonance imaging (MRI) scanner for use in a murine ischemia/reperfusion model. Phase-sensitive inversion recovery (PSIR) sequence facilitated the determination of infarct sizes in vivo by late gadolinium enhancement. Results were compared to histological infarct areas in mice after ischemia/reperfusion procedure with a good correlation (r = 0.807, P < .001 ). In addition, fractional area change (FAC) was assessed with single slice cine MRI and was matched to infarct size (r = − 0.837 ) and fractional shortening (FS) measured with echocardiography (r = 0.860 ); both P < .001 . Here, we demonstrate the use of clinical 1.5 MRI scanners as a feasible method for basic phenotyping in mice. These widely available scanners are capable of investigating in vivo infarct dimensions as well as assessment of cardiac functional parameters in mice with reasonable throughput.